SISTEM PAKAR DIAGNOSA HAMA APEL DENGAN METODE CERTAINTY FACTOR BERBASIS WEB - Arisanti, Diah; Marisa, Fitri; Wijaya, Indra Dharma (DINAMIKA DOTCOM, 2019)
An expert system is a branch of artificial intelligence and is also an emerging field of computer science as the development of computer science today. This system works to adopt human knowledge into a computer.Problems often occur on apple farm environment that is pest and so we need an agricultural consultant who is able to diagnose pest in apple crop. Problems can be a complex decision-making for their for involving multiple objectives and criteria. He built a Pest Diagnosis Expert System application Apples With Certainty Factor Method Based Web.Certainty factor calculation method using the data that came from the symptoms - symptoms of apples selected by the user on the application. Pest Diagnosis Expert System Applications Apples With Certainty Factor Method Based on this site are in accordance with refernsi obtained from experts when interviews for data retrieval, and application testing has been done with the user and obtain the respondents amounted to 73.33%, for the accuracy of the results application in addition to the system for determination of the pest must be observed to obtain correct results - absolutely accurate. Keywords, Symptoms, Hama, Diagnosis, Certainty Factor